QUALITY MANAGEMENT SYSTEM IN A HEALTHCARE ORGANISATION: FROM BASICS TO OPERATING MODEL - I.V. VINOGRADOVA; I.V. PETROV; A.A. ALMUKHAMETOV; F.S. PETROVA (Avicenna Tajik State Medical University, 2022)
Objective: To analyse the effectiveness of the quality management system (QMS) based on the amount of income for improving the quality of care in medical institutions Methods: Publications on patient safety and quality management system research were identified and analysed based on the library collection resources of the Mari State University, Yoshkar-Ola, Russia and research databases. A total of 727 results were retrieved, of which the authors preselected 121 based on keywords used; after analysing significant publications, 46 sources were finally selected. Results: The quality of medical care includes the internal audit of the quality and patient safety in hospital care. In turn, the internal audit of quality and patient safety can be limited to a "simplified model" of the quality management system. n adequately compiled, an up-to-date, applicable checklist is intended for use in the audit process. The quality of audits, the designing of effective audit procedures, and the correct completion of checklists depend on the skills and competencies of the auditor. Integrating lean manufacturing into an existing quality management system may increase the cost of "maintenance" of these systems. However, in the long term, the economic benefit will be more evident due to continuous quality improvement, cost reduction and growth of organisational maturity. The quality management system can be used as a method for assessing the effectiveness of the management process of a medical organisation at different levels: middle, auxiliary, and managerial. In this case, the quality management system becomes a superstructure over the management system based on hierarchical groups. Conclusion: A quality management system is a complex organisational model of a medical organisation that allows you to identify and improve processes, identify inconsistencies and solve them by considering the "transparency" and "understanding" of processes.